Effect of rice (Oryza sativa) bran substitution on the nutritive value of pastel buns. - Custodio, Oxanna Simon
The study focused on the effect of rice bran substitution on the nutritive value of pastel buns. Four formulations F1, F2, F3, and F4 with varying percentages of rice bran substituted to flour at 5%, 7.5%, 10%, and 12.5%, respectively, were subjected to Rank Test for Preference to determine the most preferred formulation (MPF). F2 with 7.5% rice bran was established as the MPF (Friedman?s test, α=0.05) The pastel bun prepared from the formulation F2 also designated as F2 was characterized using sensory tools and physico-chemical anayses. F2 got a like very much rating (use of 9-point hedonic scale). The substitution of rice bran significantly changed the sensory attributes of the pastel buns (Triangle Test, α=0.05) but had an insignificant effect on the preference (Paired Preference test, α=0.05). Descriptive sensory evaluation showed that F2 had chalk-like mouthfeel, slightly perceivable rice bran odor and flavor, and light brown color. There was a difference in the proximate composition between F2 and control. Rice bran substitution did not significantly reduce the moisture content of the pastel bun from 35.91% (control) to 33.21% (F2) and water activity from 0.886 (control) to 0.859 (F2). An insignificant increase in the fiber content from 1.31% (control) to 1.51% (F2) and protein from 13.80% (control) to 14.12% (F2) was also observed. In contrast, rice bran substitution significantly increased the fat content from 21.87% (control) to 24.67% (F2), ash from 0.91% (control) to 1.04% (F2), and iron content from 0.0417 mg Fe/g to 0.0500 mg Fe/g. Through these values, it can be synthesized that rice bran is can improve the protein, fiber, fat, and minerals. Consumer testing on adults and young adults shown that rice bran substituted pastel buns has a potential for commercialization.